"A Vênus moderna" - Das mulheres idealizadas nas revistas às mulheres representadas em processos criminais (Uberlândia - 1950-1980) - Silvestre, Isabelle Dias (2021)
This master's dissertation is the result of our investigation into the idealized and transgressive behaviors of social subjects, especially women, from the city of Uberlândia / MG. Through the magazines Manchete and Uberlândia Ilustrada, we verified what the idealized behavior would be like for women from the 1950s to the 1980s and with criminal proceedings we verified which behaviors were accepted and seen as deviant to the legal apparatus. In our research, we tried to analyze first the national issue, with the magazine Manchete, to understand how the behaviors are disseminated and idealized for women and then we analized the local issue with the magazine Uberlândia Ilustrada, to understand what were the behaviors disseminated in the city. At the end of the work, we tried to analyze the “real” subjects with the criminal processes of bodily injury, attempted homicide and homicide from the 1970-1980s. We verified with the criminal processes that the subjects try to fit with the behaviors disseminated by the magazines, but that in some cases, the behaviors do not fit for them. Magazines talk to the middle and upper classes and we find subjects in the middle and lower classes in the processes. Our approach, then, was the city of Uberlândia, located in the Triângulo Mineiro, between the 1950s and 1980s, and we aimed to discover the social behaviors idealized and disseminated by society in order to understand how the penalties applied in criminal processes worked, since the condemnation or acquittal was due to the idealized or transgressive behavior of the defendant and the victim.